The Paradox of Mental Health Literacy on Social Media: Between Information Accessibility and the Risk of Digital Misinformation - Citra Marhan citra; Idaman idaman; Amalia Rizqa Amalia; Sry Anugrawati Rahim; Nurmaya Nurmaya; Lia Andhriyani Rusli (Journal of Law, Social Science and Management, 2026)
Background: Social media has become a major source of mental health information, increasing access to psychoeducational content while simultaneously facilitating the spread of misinformation. Although studies have examined mental health literacy and health misinformation separately, research exploring their interaction within social media environments remains limited. Objective: This study investigated how mental health literacy functions in digital environments affected by misinformation. Specifically, it examined patterns of exposure to mental health information, the relationship between literacy and susceptibility to misinformation, and the influence of platform characteristics on users’ information processing. Methods: A sequential explanatory mixed-methods design was employed. The qualitative phase involved in-depth interviews with eight participants aged 20–26 years who actively engaged with mental health content on Instagram and TikTok. Data were analyzed using thematic analysis. A subsequent quantitative phase will involve a cross-sectional survey (target N≥400) assessing mental health literacy, digital health literacy, misinformation exposure, platform characteristics, and mental health outcomes using validated instruments. Results: Five themes emerged: increased accessibility and openness, self-diagnosis behavior, anonymity and behavioral disinhibition, stigma reduction versus reinforcement, and challenges in evaluating content credibility. Participants frequently reported difficulty distinguishing professional expertise from non-expert opinions. Conclusions: Social media presents a paradoxical environment in which greater access to mental health information coexists with increased exposure to misinformation. Strengthening digital health literacy, source evaluation skills, and platform accountability is essential to maximize benefits while minimizing potential harms. Keywords: mental health literacy, digital misinformation, self-diagnosis, online disinhibition effect, algorithmic amplification